Tinjauan Literatur Desaian Media Puzzle Interaktif Literasi Membaca Permulaan - Iin Inayati; Roshayanti, Fenny; Sulianto, Joko (Jurnal Ragam Pengabdian, 2026)
Beginning reading literacy is an essential foundation for Indonesian language learning among first grade elementary students. However, classroom findings still indicate low early reading ability caused by limited learning media that are attractive, concrete, and suitable for children’s developmental characteristics. This study aims to examine the design of interactive puzzle media as a potential instructional innovation to support beginning reading literacy for first grade students. The article employed a literature review method by analyzing thirty relevant studies published in nationally accredited Sinta indexed journals. The analysis focused on design principles, major media components, interactive puzzle characteristics, and their effectiveness in supporting early literacy skills. The findings reveal that high quality interactive puzzles contain letter, syllable, and simple word components, supported by engaging visual elements and collaborative group activities that encourage student interaction. The synthesis also demonstrates that effective puzzle designs must emphasize simplicity, gradual difficulty levels, curriculum suitability, including the topic “My Different Friends,” and integration of cognitive and social aspects. Based on literature findings and needs analysis at SD Negeri Traju this study proposes a design expected to become a practical and valid reference for first grade learning media.